Aspectos do direito à saúde em Manaus durante a pandemia de Covid-19: uma análise do dano ao projeto de vida à luz da Convenção Interamericana de Direitos Humanos, do Protocolo de San Salvador e dos standards jurisprudenciais interamericanos - Ricardo Augusto de Sales (2023)
The pandemic resulting from COVID-19 had global consequences, however it was felt most severely in countries where health conditions and the fulfillment of basic rights were already seriously compromised, as is the case in Brazil. The city of Manaus, capital of Amazonas, is a Brazilian example of these harsh consequences. The rapid growth in the number of cases caused the Manaus health network to collapse, peaking after the absence of one of the essential inputs for caring for COVID-19 patients, oxygen. The events that occurred in the city of Manaus reveal precisely the opposite of what was desired by the Inter-American Court of Human Rights - IACHR, since essential supplies were exhausted, therefore, replenishment actions were harmless, as there was no time to do so, this being the direct and immediate cause of dozens of deaths. This results in a clear violation of the rules of international law. The research is characterized, in terms of nature, as qualitative, considering that a deep interpretation of the proposed problem is carried out, with regard to the method, deductive. It was carried out with attention to legislation, doctrine and jurisprudence aimed at matters surrounding the aforementioned issues, carrying out, when appropriate, due comparison with legislation and doctrinal discussions on the topic. The study is distributed in six sections, including the introduction and conclusion, among which the concept of health and its multiple aspects are discussed, as well as the right to health from the perspective of international human rights treaties, including- if those ratified by Brazil. About the normative hierarchy of human rights treaties, public policies guaranteeing the right to health in the face of the COVID-19 pandemic, as well as about the treatment given to health in Amazonas and Manaus, during the pandemic, and its incompatibility with the treaties international human rights. The research also aims to draw a correlation between the strategic guidelines and priorities adopted by the Brazilian state, in combating the COVID-19 pandemic and the collapse of the health system in Manaus, on January 14, 2021. To this end, the issue of the biopolitics of Covid-19 in Manaus is addressed: the Manaus hospitals as necropolitical vectors of public management and human rights violations; The circumstances that preceded and directly culminated in the collapse of healthcare in Manaus, in January 2021; The ineffectiveness of the measures adopted by the Brazilian executive branch during the pandemic and the response of the judiciary, as well as the collapse of the health system, mythanasia and violations of international standards in force in Brazil. The work also focuses on the role of the judiciary and the courts of auditors, as controllers of the legality and conventionality of administrative conduct in matters of the right to health, during the pandemic associated with COVID-19. Finally, a study is carried out on civil liability for violation of the life plan in the context of the COVID-19 pandemic. In view of this, the life project and its conceptual autonomy are first outlined. Next, we discuss the relationship between damage to the life project, moral damage and existential damage; The damage to the life project and the nature of the reparation services; The principle of human dignity from the perspective of the life project; Precedents of the Inter-American Court of Human Rights and the life project, as well as the damage to the life project in the context of the COVID-19 pandemic. It is concluded, in a strict summary, that the State failed in its duty to ensure the satisfaction of the essential minimum, especially given the failure to make all the efforts that could have been made to prioritize the application of the resources at its disposal to meet these obligations.